WORST_CASE(Omega(0),?) Initial ITS Start location: l4 0: l0 -> l1 : x^0'=x^post0, z^0'=z^post0, y^0'=y^post0, (1-z^0+z^post0 == 0 /\ 1-x^0 <= 0 /\ -y^post0+y^0 == 0 /\ -x^0-z^0+x^post0 == 0), cost: 1 2: l0 -> l2 : x^0'=x^post2, z^0'=z^post2, y^0'=y^post2, (-x^0+x^post2-y^0 == 0 /\ 1-y^0+y^post2 == 0 /\ z^0-z^post2 == 0 /\ 1-x^0 <= 0), cost: 1 1: l1 -> l0 : x^0'=x^post1, z^0'=z^post1, y^0'=y^post1, (z^0-z^post1 == 0 /\ x^0-x^post1 == 0 /\ y^0-y^post1 == 0), cost: 1 3: l2 -> l0 : x^0'=x^post3, z^0'=z^post3, y^0'=y^post3, (y^0-y^post3 == 0 /\ x^0-x^post3 == 0 /\ z^0-z^post3 == 0), cost: 1 4: l3 -> l0 : x^0'=x^post4, z^0'=z^post4, y^0'=y^post4, (z^0-z^post4 == 0 /\ y^0-y^post4 == 0 /\ x^0-x^post4 == 0), cost: 1 5: l4 -> l3 : x^0'=x^post5, z^0'=z^post5, y^0'=y^post5, (x^0-x^post5 == 0 /\ z^0-z^post5 == 0 /\ y^0-y^post5 == 0), cost: 1 Applied preprocessing Original rule: l0 -> l1 : x^0'=x^post0, z^0'=z^post0, y^0'=y^post0, (1-z^0+z^post0 == 0 /\ 1-x^0 <= 0 /\ -y^post0+y^0 == 0 /\ -x^0-z^0+x^post0 == 0), cost: 1 New rule: l0 -> l1 : x^0'=x^0+z^0, z^0'=-1+z^0, -1+x^0 >= 0, cost: 1 Applied preprocessing Original rule: l1 -> l0 : x^0'=x^post1, z^0'=z^post1, y^0'=y^post1, (z^0-z^post1 == 0 /\ x^0-x^post1 == 0 /\ y^0-y^post1 == 0), cost: 1 New rule: l1 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l0 -> l2 : x^0'=x^post2, z^0'=z^post2, y^0'=y^post2, (-x^0+x^post2-y^0 == 0 /\ 1-y^0+y^post2 == 0 /\ z^0-z^post2 == 0 /\ 1-x^0 <= 0), cost: 1 New rule: l0 -> l2 : x^0'=x^0+y^0, y^0'=-1+y^0, -1+x^0 >= 0, cost: 1 Applied preprocessing Original rule: l2 -> l0 : x^0'=x^post3, z^0'=z^post3, y^0'=y^post3, (y^0-y^post3 == 0 /\ x^0-x^post3 == 0 /\ z^0-z^post3 == 0), cost: 1 New rule: l2 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l3 -> l0 : x^0'=x^post4, z^0'=z^post4, y^0'=y^post4, (z^0-z^post4 == 0 /\ y^0-y^post4 == 0 /\ x^0-x^post4 == 0), cost: 1 New rule: l3 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l4 -> l3 : x^0'=x^post5, z^0'=z^post5, y^0'=y^post5, (x^0-x^post5 == 0 /\ z^0-z^post5 == 0 /\ y^0-y^post5 == 0), cost: 1 New rule: l4 -> l3 : TRUE, cost: 1 Simplified rules Start location: l4 6: l0 -> l1 : x^0'=x^0+z^0, z^0'=-1+z^0, -1+x^0 >= 0, cost: 1 8: l0 -> l2 : x^0'=x^0+y^0, y^0'=-1+y^0, -1+x^0 >= 0, cost: 1 7: l1 -> l0 : TRUE, cost: 1 9: l2 -> l0 : TRUE, cost: 1 10: l3 -> l0 : TRUE, cost: 1 11: l4 -> l3 : TRUE, cost: 1 Eliminating location l3 by chaining: Applied chaining First rule: l4 -> l3 : TRUE, cost: 1 Second rule: l3 -> l0 : TRUE, cost: 1 New rule: l4 -> l0 : TRUE, cost: 2 Applied deletion Removed the following rules: 10 11 Eliminating location l1 by chaining: Applied chaining First rule: l0 -> l1 : x^0'=x^0+z^0, z^0'=-1+z^0, -1+x^0 >= 0, cost: 1 Second rule: l1 -> l0 : TRUE, cost: 1 New rule: l0 -> l0 : x^0'=x^0+z^0, z^0'=-1+z^0, -1+x^0 >= 0, cost: 2 Applied deletion Removed the following rules: 6 7 Eliminating location l2 by chaining: Applied chaining First rule: l0 -> l2 : x^0'=x^0+y^0, y^0'=-1+y^0, -1+x^0 >= 0, cost: 1 Second rule: l2 -> l0 : TRUE, cost: 1 New rule: l0 -> l0 : x^0'=x^0+y^0, y^0'=-1+y^0, -1+x^0 >= 0, cost: 2 Applied deletion Removed the following rules: 8 9 Eliminated locations on linear paths Start location: l4 13: l0 -> l0 : x^0'=x^0+z^0, z^0'=-1+z^0, -1+x^0 >= 0, cost: 2 14: l0 -> l0 : x^0'=x^0+y^0, y^0'=-1+y^0, -1+x^0 >= 0, cost: 2 12: l4 -> l0 : TRUE, cost: 2 Applied acceleration Original rule: l0 -> l0 : x^0'=x^0+z^0, z^0'=-1+z^0, -1+x^0 >= 0, cost: 2 New rule: l0 -> l0 : x^0'=x^0-1/2*n1^2+z^0*n1+1/2*n1, z^0'=z^0-n1, (-1+x^0 >= 0 /\ n1 >= 0 /\ -3/2+x^0+z^0*(-1+n1)+1/2*n1-1/2*(-1+n1)^2 >= 0), cost: 2*n1 Applied acceleration Original rule: l0 -> l0 : x^0'=x^0+y^0, y^0'=-1+y^0, -1+x^0 >= 0, cost: 2 New rule: l0 -> l0 : x^0'=x^0-1/2*n3^2+1/2*n3+n3*y^0, y^0'=-n3+y^0, (-1+x^0 >= 0 /\ n3 >= 0 /\ -3/2+x^0-1/2*(-1+n3)^2+1/2*n3+y^0*(-1+n3) >= 0), cost: 2*n3 Applied deletion Removed the following rules: 13 14 Accelerated simple loops Start location: l4 15: l0 -> l0 : x^0'=x^0-1/2*n1^2+z^0*n1+1/2*n1, z^0'=z^0-n1, (-1+x^0 >= 0 /\ n1 >= 0 /\ -3/2+x^0+z^0*(-1+n1)+1/2*n1-1/2*(-1+n1)^2 >= 0), cost: 2*n1 16: l0 -> l0 : x^0'=x^0-1/2*n3^2+1/2*n3+n3*y^0, y^0'=-n3+y^0, (-1+x^0 >= 0 /\ n3 >= 0 /\ -3/2+x^0-1/2*(-1+n3)^2+1/2*n3+y^0*(-1+n3) >= 0), cost: 2*n3 12: l4 -> l0 : TRUE, cost: 2 Applied chaining First rule: l4 -> l0 : TRUE, cost: 2 Second rule: l0 -> l0 : x^0'=x^0-1/2*n1^2+z^0*n1+1/2*n1, z^0'=z^0-n1, (-1+x^0 >= 0 /\ n1 >= 0 /\ -3/2+x^0+z^0*(-1+n1)+1/2*n1-1/2*(-1+n1)^2 >= 0), cost: 2*n1 New rule: l4 -> l0 : x^0'=x^0-1/2*n1^2+z^0*n1+1/2*n1, z^0'=z^0-n1, (-1+x^0 >= 0 /\ n1 >= 0 /\ -3/2+x^0+z^0*(-1+n1)+1/2*n1-1/2*(-1+n1)^2 >= 0), cost: 2+2*n1 Applied chaining First rule: l4 -> l0 : TRUE, cost: 2 Second rule: l0 -> l0 : x^0'=x^0-1/2*n3^2+1/2*n3+n3*y^0, y^0'=-n3+y^0, (-1+x^0 >= 0 /\ n3 >= 0 /\ -3/2+x^0-1/2*(-1+n3)^2+1/2*n3+y^0*(-1+n3) >= 0), cost: 2*n3 New rule: l4 -> l0 : x^0'=x^0-1/2*n3^2+1/2*n3+n3*y^0, y^0'=-n3+y^0, (-1+x^0 >= 0 /\ n3 >= 0 /\ -3/2+x^0-1/2*(-1+n3)^2+1/2*n3+y^0*(-1+n3) >= 0), cost: 2+2*n3 Applied deletion Removed the following rules: 15 16 Chained accelerated rules with incoming rules Start location: l4 12: l4 -> l0 : TRUE, cost: 2 17: l4 -> l0 : x^0'=x^0-1/2*n1^2+z^0*n1+1/2*n1, z^0'=z^0-n1, (-1+x^0 >= 0 /\ n1 >= 0 /\ -3/2+x^0+z^0*(-1+n1)+1/2*n1-1/2*(-1+n1)^2 >= 0), cost: 2+2*n1 18: l4 -> l0 : x^0'=x^0-1/2*n3^2+1/2*n3+n3*y^0, y^0'=-n3+y^0, (-1+x^0 >= 0 /\ n3 >= 0 /\ -3/2+x^0-1/2*(-1+n3)^2+1/2*n3+y^0*(-1+n3) >= 0), cost: 2+2*n3 Removed unreachable locations and irrelevant leafs Start location: l4 Computing asymptotic complexity Proved the following lower bound Complexity: Unknown Cpx degree: ? Solved cost: 0 Rule cost: 0